Contrary to endurance, power associated capacities differ between different aged and starting-nonstarting elite junior soccer players - Hoppe, M. W.; Barnics, V.; Freiwald, J.; Baumgart, C. (PLOS ONE, 2020)
This study aimed to investigate differences in anthropometric characteristics and physical capacities (1) between under (U) 17, 19, and 21 years old elite junior soccer players, and also (2) between starting and nonstarting players within each age group. Ninety-two male elite German junior field players were tested for height, mass, fat, and fat-free mass as well as aerobic endurance, squat (SJ) and counter movement jump (CMJ), linear sprint, core strength-endurance, and one repetition maximum (1RM) bench press performance. According to their age and competitive match playing times, the players were divided into the mentioned different groups. Magnitude-based inferences and effect sizes (ES) were computed for statistical analyses. The fat-free mass, SJ and CMJ, 1RM bench press, and linear sprinting performances increased likely to most likely from U17 to U21 players (ES: moderate to large), whereas the body fat, core strength-endurance, and aerobic endurance performances remain constant. The fat-free mass, 1RM bench press, and linear sprinting performances were likely to most likely higher in U21 starting compared to nonstarting players (ES: moderate to large). Our study shows that contrary to endurance, power associated capacities differ between different aged and starting-nonstarting elite junior soccer players. This outcome should be considered for training, testing, and talent selection procedures in elite junior soccer players.